A CRITICAL APPROACH OF SOCIAL ENTREPRENEURSHIP THEORIES - Cristian PIECU; Florin-Aurelian BIRCHI; Ramona-Cristina GHITA; Patricia Cristiana BORUZESCU (Management & Marketing)
Along with the evolution of society, the theories of social entrepreneurship have also evolved, and the aim of our research consists of the critical analysis of the theories related to entrepreneurial intention with a particularization of social entrepreneurship. Our research results led us to conclude that the Theory of Planned Behavior (TPB) is still a dominant theory used to measure entrepreneurial intention. However, the resource-based theory is much more oriented toward creating a genuine motivation for social entrepreneurs to transform their ideas into a social project, and the resources that the community makes available to the entrepreneurs have the potential to stimulate them to fulfill social goals. Consequently, the emotional feature of the social entrepreneur contributes to the promotion of entrepreneurial behavior oriented towards solving a specific social need of the community or society.